Accuracy of unloading with the anti-gravity treadmill - McNeill, D. K. P.; de Heer, H. D.; Bounds, R. G.; Coast, J. R. (The Journal of Strength and Conditioning Research, 2015)
Body weight (BW)-supported treadmill training has become increasingly popular in professional sports and rehabilitation. To date, little is known about the accuracy of the lower-body positive pressure treadmill. This study evaluated the accuracy of the BW support reported on the AlterG "Anti-Gravity" Treadmill across the spectrum of unloading, from full BW (100%) to 20% BW. Thirty-one adults (15 men and 16 women) with a mean age of 29.3 years (SD = 10.9), and a mean weight of 66.55 kg (SD = 12.68) were recruited. Participants were weighed outside the machine and then inside at 100-20% BW in 10% increments. Predicted BW, as presented by the AlterG equipment, was compared with measured BW. Significant differences between predicted and measured BW were found at all but 90% through 70% of BW. Differences were small (<5%), except at the extreme ends of the unloading spectrum. At 100% BW, the measured weight was lower than predicted (mean = 93.15%, SD = 1.21, p < 0.001 vs. predicted). At 30 and 20% BW, the measured weight was higher than predicted at 35.75% (SD = 2.89, p < 0.001), and 27.67% (SD = 3.76, p < 0.001), respectively. These findings suggest that there are significant differences between reported and measured BW support on the AlterG Anti-Gravity Treadmill®, with the largest differences (>5%) found at 100% BW and the greatest BW support (30 and 20% BW). These differences may be associated with changes in metabolic demand and maximum speed during walking or running and should be taken into consideration when using these devices for training and research purposes.